2015
DOI: 10.1109/tie.2014.2349363
|View full text |Cite
|
Sign up to set email alerts
|

Robust Motion Control of an Oscillatory-Base Manipulator in a Global Coordinate System

Abstract: This paper presents a control design method for motion control in a global coordinate system of an oscillatory-base manipulator, which can be regarded as a model system of mechanical systems installed on vessels or oceanic structures. This paper proposes a control design method for such systems exploiting H ∞ control and proportional and derivative (PD) control. In order to evaluate the proposed method, tracking control simulations and experiments were conducted for both attitude control and position control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Servo motors were used and it was found that the fractional-order controller reduced the transient and steady state error. In [38], an oscillatory-base manipulator was tracked using H 8 and PD controller. It used servo motors and it was found to be superior to a PID controller.…”
Section: Grippers For Known Environmentsmentioning
confidence: 99%
“…Servo motors were used and it was found that the fractional-order controller reduced the transient and steady state error. In [38], an oscillatory-base manipulator was tracked using H 8 and PD controller. It used servo motors and it was found to be superior to a PID controller.…”
Section: Grippers For Known Environmentsmentioning
confidence: 99%
“…After that, we developed an hardware experimental apparatus which consists of a two-DOF manipulator and a one-DOF base. In [83], we improved the method by employing a new weighting function for H ∞ control design, which not only reduces influence of sensor error but also enhances the robustness of the control systems; furthermore the proposed method was evaluated by simulations and hardware experiments. The results showed that the proposed control system can successfully perform in tracking control while suppressing disturbance due to the base oscillation, further even in the presence of model uncertainties due to the payload variations.…”
Section: Previous Work and Contents Of The Monographmentioning
confidence: 99%
“…Next, we present the results of D-K iteration using P augi (i = 1b, 2b) and the corresponding structured uncertainty matrices Δ ∈ 1 in (4.82) and Δ ∈ 2 in (4. 83), and this synthesis procedure means to solve the robust performance problem. The resultant upper μ bound for P augi with the index j representing the oscillation model as above has been obtained as…”
Section: H ∞ Controller Synthesismentioning
confidence: 99%
“…In tele-micromanipulation system, an H ∞ -based loop shaping method was suggested [19]. In general, this loop shaping method has been used for motion control systems [20][21][22][23][24][25][26][27][28][29][30][31][32] including commercial Hard Disk Drives [33]. In addition, for DO design, this approach was used [34][35][36].…”
Section: Introductionmentioning
confidence: 99%